Pengaruh Jumlah Persediaan Bahan Baku dan Jam Kerja Tenaga Kerja terhadap Volume Produksi : Studi Kasus pada Konveksi Seragam Sekolah Delisht Colection - Lia Nursaadah; Suci Putri Lestari; Barin Barlian (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine and analyze the effect of the variable amount of raw material inventory and labor hours on production volume. The research method used is the quantitative method and the data used is secondary data obtained directly through interviews with company owners. In this study, sampling used a periodic data approach with a semester scale of 20 samples. The variables used in this study are two independent variables and one dependent variable, so the most appropriate analysis tool is multiple linear regression. Based on the results of multiple linear analyses, it is known that the amount of raw material inventory and labor hours simultaneously and partially have a significant effect on production volume. It can also be seen from the company’s data that with every increase in the cost of controlling the number of raw materials and labor hours, the production volume also increases. The calculation results show that there is a very strong relationship between the variable amount of raw material inventory and labor hours in increasing production volume.